CATION CONTENT AND FLUXES IN RED CELLS OF NORMAL AND HYPERTENSIVE NIGERIANS (1978)
RED CELL SODIUM AND POTASSIUM CONTENT AND FLUXES IN NORMAL AND HYPERTENSIVE NIGERIANS. 1. Erythrocyte sodium, potassium and water content have been determined in 908 Nigerians so as to: 1. establish normal values in Nigerians 2. compare values in Nigerians with known values in other blacks. 3. compare values in Nigerians with those of caucasians. Red cell sodiuum, potassium and water were also determined in 7 caucasians who had been resident in Nigeria for periods varying from 6 months to 18 years. The RBC sodium for Nigerians considerably higher than those of caucasians, but the RBC potassium and water did not show any significant difference. In the course of this work, the normal (control) subjects were grouped according to their genotypes. 3 genotypes were encountered: AA, AS and AC. There was no significant difference in the erythrocyte sodium, potassium and water of the individuals belonging to these 3 genotypes. The results were also analysed for sex and age differences, and none was found. Results of erythrocyte sodium, potassium and water from 3 siblings and their mother were also presented. These results differed, from one another, suggesting that environmental factors are also important and probably just as potent determinants of RBC sodium, potassium and water content as are genetic factors. 2. 100 hypertensive subjects were studied. They were all newly diagnosed, mostly symptomless ambulant subjects who were attending the medical out-patient department of the University College Hospital, Ibadan. Their main pathological finding systemic hypertension. They were followed up for periods varying from 18 months to 3 1/2 years. Investigations were performed on each patient which enabled their being grouped into hypertensives with normal renal function or hypertensives with abnormal renal function. Only those with normal renal function were included in the study. The results obtained for the red cell sodium and potassium were significantly different from those of the Controls. Their red cell water was also significantly different from that of the Controls, but the difference m RBC water was not sufficient to account for the differences in the RBC sodium and potassium. Here again, the RBC sodium and potassium were not related to age or sex. The RBC sodium and potassium content were in no way related to the mean blood pressures. Their values remained the same both before and during treatment. Adequate control and maintenance of the patients blood pressures within the normal range did not affect these two cations. 3. When red cells from Controls and red cells from Hypertensives were exposed to a high sodium load, the RBCs from hypertensive gained a lot more sodium and lost a lot more potassium than the RBCs from Controls. 4. Normal red cells lost their potassium into isotonic sucrose media seven times as fast as red cells from hypertensive subjects. 5. Normal red cells have a slightly higher a tive sodium flux per hour than red cells from hypertensive subjects, but the difference is not statistically significant. The rate constant for active sodium flux is higher for red cells of Controls than for red cells of hypertensive subjects, but the correlation between intracellular sodium content and rate constant is not good (r= -0.43). The rate constant for the red cells of the hypertensives is lower, but it correlates better with the red cell sodium (r =0.53).